Positive information from equity issue announcements - Cooney, John W.; Kalay, Avner (Journal of Financial Economics, 1993)
The Myers and Majluf (1984) model predicts a nonpositive price reaction to an announcement of a new issue of equity. This paper shows that the Myers and Majluf result is a direct outcome of their assumption that all potential projects facing the firm have a nonnegative net present value. Refining the Myers and Majluf model, by allowing for the realistic possibility of potential projects having negative net present values, leads to different predictions. The refined model predicts positive as well as negative stock price responses, consistent with recent empirical evidence concerning the stock price effects of new stock issues.